Strawberries in Winter - Najade, Freya (Design/Arts/Culture, 2023)
The series Strawberries in Winter provides a visual representation of the evolving agricultural landscape, highlighting the impact of modern agricultural practices within the context of capitalism. In the current state of agriculture, where the demands of supermarkets and consumers for year-round availability, consistent quality and low prices have led to significant changes in farming practices. The pressure to produce more on the same land, utilizing advanced technology and scientific advancements, has led to the expansion of farms, increased mechanization, and a shift away from the traditional rhythms of nature. The imagery of Strawberries in Winter symbolizes this dissociation from natural cycles and the disconnection from traditional modes of agriculture. In essence, it depicts a changed agricultural landscape that is shaped by profit-driven practices, consumer demands, a growing population and technological advancements, which collectively contribute to the reimagining of nature and reality to fit within the constraints of a capitalist framework.